Partial fiscal decentralization and local government spending policy - Agnieszka Kopańska (e-Finanse: Financial Internet Quarterly, 2018)
The aim of this paper is to analyze how limits in revenue and spending autonomy of sub-sovereign governments influence their decisions. Revenue and spending autonomy indicators for Polish towns were established and used in analysis on school education expenditures during 2003-2016. The influence of limits on revenue autonomy on municipal spending has been extensively addressed in both theoretical and empirical literature. However, studies related to spending autonomy are rare. The analysis presented in this paper suggests that when limits exist in spending autonomy, more decentralized tasks are crowded out by regulated obligations. That is why the spending autonomy analysis is important to evaluate the equity between local units and the adequacy of local revenues to decentralized expenditures. The basic principle of local finance is that there should be an adequate relationship between the financial resources available to a local authority and the tasks it performs. However, in practice, the assessment of whether this has been achieved is very difficult. Often, only problems with the solvency of local governments indicate that we are dealing with a poorly constructed system of local finances. The expenditure autonomy indicator proposed in this article is a tool that provides a way to indicate problems with the adequacy of revenues before such an extreme situation occurs.
Keywords: H72; H75; H77; 330; partial decentralization; spending and revenue autonomy; local government spending policy